Proteome profile changes during poly-hydroxybutyrate intracellular mobilization in gram positive Bacillus cereus tsu1 - Li, Hui (BMC Microbiol, 2020)
BACKGROUND: Bacillus cereus is a bacterial species which grows efficiently on a wide range of carbon sources and accumulates biopolymer poly-hydroxybutyrate (PHB) up to 80% cell dry weight. PHB is an aliphatic polymer produced and stored intracellularly as a reservoir of carbon and energy, its mobilization is a key biological process for sporulation in Bacillus spp. Previously, B. cereus tsu1 was isolated and cultured on rapeseed cake substrate (RCS), with maximum of PHB accumulation reached within 12 h, and depleted after 48 h. Fore-spore and spore structure were observed after 24 h culture. RESULTS: Quantitative proteomic analysis of B. cereus tsu1 identified 2952 quantifiable proteins, and 244 significantly changed proteins (SCPs) in the 24 h:12 h pair of samples, and 325 SCPs in the 48 h:12 h pair of samples. Based on gene ontology classification analysis, biological processes enriched only in the 24 h:12 h SCPs include purine nucleotide metabolism, protein folding, metal ion homeostasis, response to stress, carboxylic acid catabolism, and cellular amino acid catabolism. The 48 h:12 h SCPs were enriched into processes including carbohydrate metabolism, protein metabolism, oxidative phosphorylation, and formation of translation ternary structure. A key enzyme for PHB metabolism, poly(R)-hydroxyalkanoic acid synthase (PhaC, KGT44865) accumulated significantly higher in 12 h-culture. Sporulation related proteins SigF and SpoEII were significantly higher in 24 h-samples. Enzymes for nitrate respiration and fermentation accumulated to the highest abundance level in 48 h-culture. CONCLUSIONS: Changes in proteome of B. cereus tsu1 during PHB intracellular mobilization were characterized in this study. The key enzyme PhaC for PHB synthesis increased significantly after 12 h-culture which supports the highest PHB accumulation at this time point. The protein abundance level of SpoIIE and SigF also increased, correlating with sporulation in 24 h-culture. Enzymes for nitrate respiration and fermentation were significantly induced in 48 h-culture which indicates the depletion of oxygen at this stage and carbon flow towards fermentative growth. Results from this study provide insights into proteome profile changes during PHB accumulation and reuse, which can be applied to achieve a higher PHB yield and to improve bacterial growth performance and stress resistance.